Konsep dan Fungsi Perumpamaan Al-Qur’an (Amtsal) sebagai Pendekatan Retorika dalam Menyampaikan Nilai-Nilai Moral dan Spiritual - Annisa Nasputri; Refa Ekila Nurhuda; Fahreza Gempita; Riska Sawitri (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Qur’anic parables (amtsal) represent a rhetorical approach used in the Qur’an to convey messages of faith, morality, and guidance for human life. Through parables, abstract concepts are presented in more concrete forms, making them easier to understand and more influential in shaping moral and spiritual attitudes. This study aims to examine the concept and function of Qur’anic parables (amtsal) as a rhetorical approach to conveying moral and spiritual values. The research employs a qualitative approach using a library research method by analyzing relevant literature in the fields of Qur’anic studies and exegesis. The findings reveal that Qur’anic parables consist of several main forms, namely amtsal musharrahah, amtsal kaminah, and amtsal mursalah, each possessing distinctive rhetorical characteristics and educational functions. Furthermore, Qur’anic parables serve as an effective medium for explaining abstract concepts, instilling moral and spiritual values, encouraging positive behavior, and strengthening faith. Therefore, the rhetorical use of parables in the Qur’an plays a strategic role in fostering the internalization of moral and spiritual values in human life